Field-Effect Sensors From pH Sensing to Biosensing - Schöning, Michael J.; Ingebrandt, Sven (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue focuses on fundamental and applied research on different types of field-effect chemical sensors and biosensors. The topics include device concepts for field-effect sensors, their modeling, and theory as well as fabrication strategies. Field-effect sensors for biomedical analysis, food control, environmental monitoring, and the recording of neuronal and cell-based signals are discussed, among other factors.